Hindrances to pupils’ access and participation in primary school education in Kakuma and Lokichoggio divisions, Turkana county - Migosi, Joash; Nanok, Daniel; Ombuki, Charles; Metet, Joseph (Transnational Research Journals, 2012)
This study was undertaken to investigate pupils’ access and participation challenges in primary school education in Kakuma and Lokichoggio divisions of Turkana County in North Western Kenya. The purpose of the study was to investigate factors that hinder pupils’ access and participation in primary school education in Turkana County, using Kakuma and Lokichoggio divisions as case study. The two divisions’ nine schools were randomly selected to form the sample population for the study. The research study employed the descriptive survey design. The data collection instruments utilized included questionnaires administered to head teachers and teachers, focus group discussions conducted for pupils and parents and interview guides done for the key informants and head teachers. The data collected was analysed using descriptive statistics. The study, paradoxically, revealed that financial resources played insignificant role in school access whereas cultural factors, parental negligence and ignorance of their roles in education provision, poverty among the majority of parents and insecurity played a major role in hindering education access and participation in the area. This study recommends that more boarding schools be established in the area of study. The study also recommends that a sensitization programmed be undertaken for education stakeholders in the area to improve understanding of their roles and responsibilities in the provision of education opportunities to learners. Keywords: Hindrances, pupils’ access, pupils’ participation, primary school, Kakuma, Lokichoggio, Turkana